Inflammation and Elevation of Interleukin-12p40 in Patients with Schizophrenia - Bedrossian, Nora; Haidar, Mariam; Fares, Jawad; Kobeissy, Firas H.; Fares, Youssef (Frontiers in Molecular Neuroscience, 2016)
Schizophrenia is a serious mental illness with chronic symptoms and significant impairment in psychosocial functioning, which suggests that it likely has neurodegenerative characteristics. Inflammatory markers such as pro-inflammatory cytokines are well-known etiological contributors for psychiatric disorders, including schizophrenia. Although, the role of inflammation in schizophrenia is becoming evident, the number of studies in this area is relatively scarce, especially in Lebanon, and increased procedural thoroughness is needed. Cytokines play a key role in the activation of the immune system and strongly influence neurotransmission. Previous investigation of plasma levels showed dysregulation of interleukin (IL)-12. However, genotypical variations of this interleukin have not been investigated for patients with schizophrenia yet. Thus, in this paper, we aimed to compute and assess IL-12p40 levels in the sera of individuals with schizophrenia from different provinces in Lebanon and compare it to controls. Healthy subjects comprised 60 individuals with a male/female (M/F) ratio of 31/29, whereas patients with schizophrenia consisted of 63 subjects with an M/F ratio of 30/33. The mean age for healthy controls was 30 years, whereas that for patients with schizophrenia was 35 years. A standardized enzyme-linked immunosorbent assay (ELISA) technique was used to measure the concentration of IL-12p40 in all collected sera (n = 123). The mean IL-12p40 levels in patients with schizophrenia were significantly higher than in healthy controls (p = 0.002). Healthy females had a significantly higher concentration of IL-12p40 than healthy males (p = 0.009). Female patients with schizophrenia had significantly higher concentrations of IL-12p40 than their male counterparts (p < 0.001), healthy females (p = 0.018), and healthy males (p < 0.001), respectively. Male patients with schizophrenia had significantly higher concentrations of IL-12p40 than healthy males (p = 0.023). The study’s results suggest that IL-12p40 has a putative role as a potential marker in schizophrenia and that its elevation may participate in its pathogenesis. IL-12p40 may be included in a panel to be evaluated in the sera of patients with schizophrenia and an appreciation of its independent function is important for improving our understanding of both protective and pathogenic immune responses. Future research should aim to assess this interleukin and understand its role in other mental illnesses that share a similar etiology to schizophrenia.